Skill Level of Playing Indonesian Men's National Outdoor Hockey Team: Tingkat Keterampilan Bermain Tim Nasional Hockey Outdoor Putra Indonesia - Ali Budiman; Rama Adha Septiana; Muhammad Riandzi Syam (Journal of Physical and Outdoor Education, 2022)
The purpose of this study was to find out how big the playing skills of the Indonesian men's National Outdoor Hockey Team are. The population in this study was the athletes of the Indonesian men's outdoor hockey national team, totaling 16 people. The sampling technique used is purposive sampling, which means a sampling technique by determining certain criteria. The instrument in this study used Games Performance Assessment Instrument Components (GPAI). The research method used is descriptive quantitative with a survey approach. The data collection techniques in this study were directly and analyzed using the percentage formula and the GPAI calculation formula with the requirements for calculating data analysis using the average value calculation. very good category with 0 matches or 0%, good category 5 matches or 100%, enough category 0 matches or 0% and 0 matches or 0% for less category. Based on this, it can be concluded that the skill level of playing the Indonesian men's outdoor hockey national team is in the good category, but still needs to improve the effectiveness of the game and other aspects in order to be able to excel at the international level.